Interactive aesthetic experience and individuation: Some reamrks on U-DATInos (Itinera, 2022)
Starting from the analysis of U-DATInos, an artistic project realised by Salvatore Iaconesi and Oriana Persico, the article intends to investigate the essential traits and conditions of possibility of the interactive aesthetic experience. In order to understand the phenomenon of interactivity from a philosophical point of view, it may be of some interest to take a closer look at the concept of relation. The topic will be developed by comparing the perspectives of Gilbert Simondon and Alfred N. Whitehead. The primacy of the relation is precisely the phenomenon that both Simondon and Whitehead, independently but not incompatibly, sought to highlight. A relationship rich in consequences is thus formed between art and philosophy. Philosophy is enriched by its contact with artistic practices, reconsidering the categories it has at its disposal or creating new ones; in doing so, it provides art theory with the conceptual tools it needs, without, however, claiming to reduce the meaning of art within the dimension of the concept.